Development of a digital media-based curriculum for early childhood at aisyiyah kindergarten, karangwaru plupuh, sragen - Ngatmin Abbas (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to explore and develop a curriculum model based on the integration of digital media for early childhood education at Aisyiyah Kindergarten in Karangwaru Plupuh, Sragen. In the context of rapid technological advancement, this research is guided by the primary question: To what extent does the current curriculum support the integration of digital media in early childhood learning, and how can the curriculum be further developed to be more adaptive to technological demands? This research employs a qualitative descriptive method, utilizing in-depth interviews with two key informants: the head of the kindergarten and an experienced early childhood education teacher, both of whom have more than 19 years of service. The findings indicate a level of awareness and partial implementation of digital media—such as laptops, tablets, and smartphones—in learning activities. Although both informants have attended training on the use of digital media and occasionally incorporate such tools into their teaching, several challenges persist. These challenges include uneven technical readiness, a lack of collaborative planning among teachers, and the absence of a curriculum that structurally supports digital-based learning. Interestingly, both educators noted that digital media often aids in enhancing children's understanding of the subject matter, and parental support for its usage is relatively positive. However, the existing curriculum is deemed insufficiently responsive to the integration of technology. This study underscores the importance of developing a curriculum that not only acknowledges the presence of digital technologies but also provides tangible support to teachers through clear guidelines, training, and institutional collaboration. The proposed curriculum model has the potential to serve as a foundation for creating a more adaptive and future-oriented early childhood education system.